La réponse sécuritaire de l’administration Bush : l’USA PATRIOT Act et les libertés individuelles - Alice GAIRARD-BERNARD (E-REA)
One of the key actions taken by the Bush administration was to push for the adoption of the USA PATRIOT Actin order to address the needs of a country following an unprecedented terrorist attack. While most aspects of the legislation are not controversial, a few sections giving the government greater surveillance powers raise civil liberties issues. Of interest is the reaction to this impaired mechanism of checks and balances – bi-partisan initiatives to restore checks and balances stemming from a few congressmen, lawsuits challenging the controversial parts of the law, several public interest groups, notably the ACLU, calling for adequate judiciary oversight, greater accountability of agencies involved in surveillance programs and restored protection for civil rights, and grassroots movements leading towns, cities and later counties and states to adopt resolutions rejecting the USA PATRIOT Act.